LZK-dependent stimulation of astrocyte reactivity promotes corticospinal axon sprouting - Chen, Meifan; Ingle, Laura; Plautz, Erik J.; Kong, Xiangmei; Tang, Rui; Ghosh, Neil; Romprey, Megan K.; Fenske, William K.; Goldberg, Mark P. (Frontiers in Cellular Neuroscience, 2022)
Injury to the adult mammalian central nervous system induces compensatory plasticity of spared axons – referred to as collateral axon sprouting – that can facilitate neural recovery. The contribution of reactive astrocytes to axon sprouting remains elusive. Here, we sought to investigate the role of axon degeneration-reactive astrocytes in the regulation of collateral axon sprouting that occurs in the mouse spinal cord after unilateral photothrombotic stroke of the primary motor cortex. We identified astrocytic leucine zipper-bearing kinase (LZK) as a positive regulator of astrocyte reactivity to corticospinal axon degeneration. Remarkably, genetic stimulation of astrocyte reactivity, via LZK overexpression in adult astrocytes, enhanced corticospinal axon sprouting. LZK promoted the production of astrocyte-derived ciliary neurotrophic factor (CNTF) that likely enhanced axon growth in mice with astrocytic LZK overexpression after injury. Our finding that LZK-dependent stimulation of astrocyte reactivity promotes corticospinal axon sprouting highlights the potential of engineering astrocytes to support injury-induced axon plasticity for neural repair.